ANALYSIS OF SELLING COST OF HARVESTED DRY GRAINS IN WOWASOLO VILLAGE, WANGGEDUKU DISTRICT, KONAWE REGENCY - Nurcayah; Syamsinar; Basri Sufa (Fakultas Pertanian Universitas Muhammadiyah kendari, 2024)
This study was conducted in October - November 2023, aiming to determine the cost of selling dry harvested grain and the minimum selling price of dry harvested grain in Wowasolo Village, Wanggeduku District, Konawe Regency. Data collection using a structured interview method with each respondent. The data analysis method used to calculate the total production costs is calculated using the formula TC = FC + VC, while to calculate the cost of goods sold the author uses the formula: Cost of goods sold (Rp / kg) = total cost (Rp) divided by the amount of production produced (Kg). To calculate the minimum selling price of dry harvested grain the author uses the formula: 10% x HPP. The results of the study obtained the total cost of Rp. 6,431,989 / farmer and the cost of goods sold: Rp. 2.859 Kg / Kg. The minimum selling price of dry harvested grain obtained results of Rp. 3,145 / Kg. This farmer's HPP is much smaller than the HPP set by the government at IDR 4,200/kg (Decree of the Minister of Trade No. 24 of 2020